Histopathologic evaluation of wooden breast and white striping myopathy in different broiler genotypes using light microscopy and image analysis - Zehra Avci-Kupeli; Erdem Caglar-Kupeli; Metin Petek (Revista Científica)
Broiler myopathies cause significant economic losses in the poultry industry, adversely affecting meat quality and animal welfare. Cobb 500 and Ross 308 are widely cultivated commercial lines globally; however, Anadolu–T is a newly developed genotype with limited research on the histopathological evaluation of myopathic lesions. This study focuses on the histopathological evaluation of breast muscle myopathies in three different broiler lines (Cobb 500, Anadolu–T, and Ross 308). Additionally, histopathological lesions such as lipidosis, inflammatory cell infiltration, connective tissue formation, and degeneration were compared among genotypes using manual scoring with traditional light microscopy, as well as less commonly utilized digital image analysis software, including ImageJ and QuPath. Macroscopically, the Cobb genotype exhibited the highest WB scores (mean score: 2) (P<0.05), while the Anadolu–T genotype had the highest WS scores (1.11) (P>0.05). In the evaluation of histopathological lesions, the highest fibrosis scores were observed in the Cobb genotype (0.86), the highest mononuclear inflammatory cell infiltration scores in the Ross genotype (2.25), the highest lipidosis scores in the Anadolu–T genotype (3.22), and the highest degeneration scores in the Cobb genotype (3) (P>0.05). In this study, the evaluation of myopathy scores revealed significant differences in myopathy susceptibility among different genotypes. The Anadolu–T genotype was found to be less susceptible to WB myopathy severity (P<0.05) but more prone to WS myopathy severity (P>0.05).